Potent enhancement of GFP uptake into HT-29 cells and rat skin permeation by coincubation with tat peptide - Lohcharoenkal W. (2014)
The delivery enhancements of green fluorescent protein (GFP), a model reporter protein into/transepithelial colon adenocarcinoma (HT-29) cells and excised rat skin by coincubation, by simple mixing or as fusion protein with HIV1-trans-activating transcriptional (Tat), a cell-penetrating peptide, have been described. By simple mixing, Tat/GFP mixture could increase the cellular uptake of GFP into HT-29 cells by 4.25-fold and 1.79-fold of GFP and Tat-GFP fusion protein, respectively. The incubation time showed no effect on the cellular uptake of Tat/GFP and Tat-GFP. In transepithelial study, Tat-GFP demonstrated the highest ability to penetrate through the HT-29 cells of about 1.3-fold and 1.2-fold of GFP and Tat/GFP, respectively. Only Tat/GFP gave lower cytotoxicity than Tat or GFP alone. In transdermal delivery study, Tat/GFP showed better transdermal delivery profile with higher cumulative amount than Tat-GFP in stratum corneum (SC), viable epidermis and dermis, and the receiver compartment of the diffusion cell with the highest fluxes of 7.42 and 35.6; 8.87-fold and 5.57-fold of GFP and Tat-GFP in SC and receiver compartment, respectively. This study demonstrated an efficient enhancement of GFP uptake into cells and through excised rat skin by simple mixing with Tat peptide, which can be further applied for the development of protein drug delivery systems. © 2011 Wiley-Liss, Inc.